LANGSTON HUGHES AND HIS POETRY - Karimboyeva Sevinchoy Muzaffar qizi (Лучшие интеллектуальные исследования, 2024)
Langston Hughes is a representative of the Blacks, an evidence of African- American’s sufferings. He is known for registering the sufferings faced by the Blacks in the hands of Whites in his poems. He presents America is the affluent society only for Whites and the segregated society for the Blacks. This close discrimination is well-presented in his poems. His poems are not an imaginary illustration of unregistered evils directed against the Blacks and he proves a rebel with a firm resolve to prepare the people for a struggle and make them agitate for the poor’s emancipation from the hegemony of the domineering race, White. At the core, this paper describes Langston Hughes as a champion of the Blacks and dwells on their passionate identification with it. His poems reflects his anger against the White capitalists is also discussed.